Doping-Promoted Solar Water Oxidation on Hematite Photoanodes - Zhang, Yuchao (Molecules, 2016)
As one of the most promising materials for solar water oxidation, hematite has attracted intense research interest for four decades. Despite their desirable optical band gap, stability and other attractive features, there are great challenges for the implementation of hematite-based photoelectrochemical cells. In particular, the extremely low electron mobility leads to severe energy loss by electron hole recombination. Elemental doping, i.e., replacing lattice iron with foreign atoms, has been shown to be a practical solution. Here we review the significant progresses in metal and non-metal element doping-promoted hematite solar water oxidation, focusing on the role of dopants in adjusting carrier density, charge collection efficiency and surface water oxidation kinetics. The advantages and salient features of the different doping categories are compared and discussed.